Circulating endocannabinoids and prospective risk for depression in trauma-injury survivors - Fitzgerald, Jacklynn M. (Neurobiol Stress, 2021)
Biological mechanisms associated with response to trauma may impact risk for depression. One such mechanism is endocannabinoid signaling (eCB), a neuromodulatory system comprised of the CB1 subtype of cannabinoid receptors (CB1R), encoded by the CNR1 gene, and two primary endogenous ligands: 2-arachidonoylglycerol (2-AG) and N-arachidonylethanolamine (AEA), hydrolyzed by monoacylglycerol lipase (gene name MGLL) and fatty acid amide hydrolase (gene name FAAH). Preclinical data suggest that eCB/CB1R signaling acts as a stress buffer and its loss or suppression increases depression-like behaviors. We examined circulating concentrations of the eCBs (2-AG and AEA) days and six months after a traumatic injury as a marker of eCB/CB1R signaling and as predictors of Center for Epidemiologic Studies of Depression Scale-Revised [CESD-R] scores as a measure of depression severity six months after injury. We also explored associations of CNR1, FAAH, and MGLL genetic variance with depression severity at six months. Results from hierarchical multiple linear regressions showed that higher 2-AG serum concentrations after trauma predicted greater depression at six months (β = 0.23, p = 0.007); neither AEA after trauma, nor 2-AG and AEA at six months were significant predictors (p's > 0.305). Carriers of minor allele for the putative single nucleotide polymorphism in the CNR1 gene rs806371 (β = 0.19, p = 0.024) experienced greater depression at six months. These data suggest that the eCB signaling system is highly activated following trauma and that eCB/CB1R activity contributes to long-term depression risk.